H∞ output feedback control of networked control systems with multiple quantisers. (2015) - Yu, Mei; Bai, Shuang; Zhang, Jianhua
H∞ output feedback control of a kind of multi-input and multi-output networked control system (NCS) with packet loss processes is considered in this paper, where the packet loss processes are modelled by independent Markov chains. Multiple quantisers are located at both of the sensor nodes and the controller nodes. For each quantiser, the quantisation density varies with the successive packet dropout number that the corresponding quantised signal experiences. A sufficient condition of the exponential stability with a prescribed H∞ performance level is developed based on the Lyapunov-Krasovskii function approach. Then, a quantised dynamic output feedback controller is designed via a cone complement linearisation method. Finally, a simulation result is provided to demonstrate the effectiveness of the designed method.